Navigating challenges and opportunities in urban circular bioeconomy: A comprehensive review and future directions - Bertolucci Paes, Luis Alberto; Bezerra, Barbara Stolte [UNESP]; Jugend, Daniel [UNESP]; Liar Agudo, Fabiana (Elsevier, 2024)
Urban ecosystems face several challenges in implementing the circular bioeconomy, including financial limitations, a lack of coordinated public policies, insufficient valorisation of biowaste, and a lack of commitment to supporting practices that encourage the creation of socio-ecological values on the part of the actors shaping the narrative. Despite global efforts to consolidate circular practices, policies addressing the bioeconomy, particularly in urban ecosystems, remain ambiguous concerning the availability of resources and the value of ecosystem services. To address these gaps, we conducted an integrative literature review centred on the underlying constructs that drive the development of narratives. We identify several critical factors, such as public-private partnerships, political support for circular initiatives, and collaboration with local authorities. We also advocate and propose the synergy of decentralisation and colocation practices and the need to promote low-entropy urban ecosystems. By highlighting the theoretical links between definitions, core constructs, and essential practices, this paper outlines approaches to assessing the impact of the urban circular bioeconomy on sustainable development. By further investigating these links, the paper provides valuable information and recommendations for future research.
Keywords: Circular economy; Collaborative governance; Ecosystem service; Social dynamics; Urban ecology